The Effect of Work Motivation and Quality of Work Life on the Performance of Employees of the Regional House of Representatives Secretariat in Penajam Paser Utara Regency - Hapdayani, Hapdayani; Hamid, Muliyadi; Suyuthi, Nurmadhani Fitri (Journal of Management and Administration Provision, 2023)
This study aims to analyze the influence of work motivation and Quality of Work Life (QWL) on employee performance at the Secretariat of DPRD in Penajam Paser Utara Regency. The specific objectives of this research are: 1) to determine and analyze the effect of work motivation on employee performance, 2) to determine and analyze the effect of QWL on employee performance, and 3) to determine and analyze the simultaneous effect of work motivation and QWL on employee performance. The research was conducted at the Secretariat of DPRD in Penajam Paser Utara Regency, East Kalimantan, over a period of approximately 3 months from the submission of the research proposal. The total number of respondents involved in this study was 104 employees, who were selected as the sample. The data analysis method used is multiple linear regression analysis to test the effects of independent variables (work motivation and QWL) on the dependent variable (employee performance). Regression coefficient statistical tests are used to determine the significance of the effects of independent variables on the dependent variable. The results of the study indicate that: 1) Work motivation has a positive and significant effect on employee performance at the Secretariat of DPRD in Penajam Paser Utara Regency. This finding is consistent with the majority of previous studies, which show that work motivation plays a crucial role in enhancing productivity and service quality. 2) Quality of Work Life (QWL) also has a positive and significant effect on employee performance, where a comfortable and supportive work environment contributes to job satisfaction, reduces stress, and increases employee productivity. 3) Simultaneously, both work motivation and QWL have a significant effect on employee performance, with these two variables explaining a substantial portion of the variation in employee performance. These findings emphasize that both work motivation and QWL are essential in creating a supportive work environment that motivates employees to achieve optimal results.